Analysis of a selected motorbike suspension component with the use of CAD modelling and finite element method - Bik, Tomasz (Advances in Mechanical and Materials Engineering, 2017)
Modelling procedure as well as structural and modal analyses of high-performance motorbike suspension element are presented in this article. Siemens NX 8.5 system has been used while preparing CAD model of components. The numerical analyses have been performed based on Finite Element Method (FEM) in ANSYS Workbench package. The behaviour of the considered part that reflects its working conditions has been set by defining appropriate loads, boundary conditions and de-sign assumptions. As a result of the performed analyses, stress and strain distribu-tions as well as selected natural vibration modes have been received. On the basis of these results the conclusions and further research directions have been formulated.